2022
DOI: 10.3390/cancers14163848
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Prediction of Five-Year Breast Cancer Recurrence in Women Who Receive Neoadjuvant Chemotherapy

Abstract: In current clinical practice, it is difficult to predict whether a patient receiving neoadjuvant chemotherapy (NAC) for breast cancer is likely to encounter recurrence after treatment and have the cancer recur locally in the breast or in other areas of the body. We explore the use of clinical history, immunohistochemical markers, and multiparametric magnetic resonance imaging (DCE, ADC, Dixon) to predict the risk of post-treatment recurrence within five years. We performed a retrospective study on a cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The model revealed that k-nearest neighbour (KNN) and predictive mean matching (PMM) imputations provide close maximum area under ROC curves, 0.6428 (at 60% missingness with MAR mechanism) and 0.6418 (at 30% of missing data with MCAR mechanism) respectively. A study [ 41 ] demonstrated the ability to predict or discriminate the recurrence from non-recurrence cases of breast cancer prior to ‘neo-adjuvant chemotherapy’ treatment yield area under ROC curve of 75%; a difference of about 11% compared to ours. This implies that the imputed data via KNN and PMM are most plausible to enable classifiers to separate breast cancer recurrence cases for at least 64%.…”
Section: Discussionmentioning
confidence: 71%
“…The model revealed that k-nearest neighbour (KNN) and predictive mean matching (PMM) imputations provide close maximum area under ROC curves, 0.6428 (at 60% missingness with MAR mechanism) and 0.6418 (at 30% of missing data with MCAR mechanism) respectively. A study [ 41 ] demonstrated the ability to predict or discriminate the recurrence from non-recurrence cases of breast cancer prior to ‘neo-adjuvant chemotherapy’ treatment yield area under ROC curve of 75%; a difference of about 11% compared to ours. This implies that the imputed data via KNN and PMM are most plausible to enable classifiers to separate breast cancer recurrence cases for at least 64%.…”
Section: Discussionmentioning
confidence: 71%
“…Using multimodal data is another solution for improving the prediction performance. Recent studies [ 32 34 ] in this emerging field have shown accurate prediction ability has further improved. Future research should prioritize the incorporation of additional modalities to establish a comprehensive multimodal representation approach.…”
Section: Discussionmentioning
confidence: 99%
“…There was currently no study using the MARS model to predict the prognosis for BC patients, to the best of our knowledge. Several articles using different ML models to predict the prognosis of BC patients aroused controversy [ 7 9 , 14 16 , 20 , 25 28 , 57 ]. Firstly, Kate et al [ 7 ] believed that NB was better than DT and LR through the research on more than 160000 BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since ML models were susceptible to factors such as data sources, input variables, and software, several articles using ML to predict the prognosis of BC patients were controversial [ 7 9 , 12 – 16 , 20 , 25 28 ]. Lotfnezhad Afshar et al [ 9 ] believed that support vector machine (SVM) model outperformed other models in the predicting the survival rate of BC patients.…”
Section: Introductionmentioning
confidence: 99%